MSMEs Development Strategy Using the Canvas Business Model, Islamic Economic Review (Case Study of MPOK ATIK Peanut Bread, Tebing Tinggi City) - Masitha Khairani Hasibuan; Wahyu Syarvina; Ahmad Muhaisin B Syarbaini (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The purpose of this study is to analyze the development strategy of Mpok Atik's peanut bread MSME using the Canvas Business Model and to determine whether the development strategy aligns with Islamic values. This study uses descriptive research, where researchers explore and collect data directly in the field using a qualitative approach. The Business Model Canvas is a comprehensive, simple business model consisting of nine main elements. Within the context of Islamic thought, each element can be adapted to Sharia principles. In general, Islamic economic principles differ from other economic principles. Islamic economics prioritizes not only profit or income but also the pursuit of Allah's blessings. The ultimate goal of Islamic economics is the same as Islamic law itself: achieving prosperity in this world and the hereafter through a good and honorable lifestyle (haiyah taiyiba).